RELATIONSHIP BETWEEN WORK PERIOD, WORK POSTURE, WORK CLIMATE, AND NOISE WITH WORK FATIGUE AT CHARCHOAL BRIQUETTE INDUSTRY WORKERS - Ekawati, Ekawati; Amalia, Hidayatul; Kurniawan, Bina (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Work fatigue is a problem that can affect all workers in carrying out their work. Workers in the charcoal briquette industry are at risk of experiencing work fatigue. This study was conducted to analyze the relationship between work period, work posture, work climate, and noise with job fatigue in charcoal briquette industry workers. The study was an observational analytic type with a cross sectional approach. The sample of this study was determined by purposive sampling technique with sample criteria, namely workers not in the curing section, totaling 30 people. The research instruments were a respondent data sheets, IFRC questionnaire, RULA sheet, Angle Meter application, Area Heat Stress Monitor, and Sound Level Meter. The statistical test used was the Spearman Rank correlation test. The results showed that most of the respondents had a new working period, very risky work posture, work climate exposure above the NAB (>28ºC), noise exposure below the NAB (≤85 dBA), and mild fatigue. The Spearman Rank Correlation test results showed that there was a relationship between work posture (p-value = 0.022), work climate (p-value = 0.045), and noise (p-value = 0.000) with work fatigue. In contrast, work period was not associated with work fatigue (p-value = 0.0486)